2010
DOI: 10.1159/000302902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fluoride Concentrations of Experimental Dentifrices on Enamel Erosion and Abrasion

Abstract: It has been suggested that fluoride products are able to reduce erosive tooth wear. Thus, the purpose of this in vitro study was to evaluate the effect of dentifrices with different fluoride concentrations as well as of a low-fluoridated dentifrice supplemented with trimetaphosphate (TMP) on enamel erosion and abrasion. One hundred twenty bovine enamel blocks were assigned to the following experimental dentifrices: placebo, 1,100 µg F/g, 500 µg F/g plus 3% TMP and 5,000 µg F/g. The groups of enamel blocks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 69 publications
3
97
0
7
Order By: Relevance
“…Several studies have suggested that TMP reduces the demineralization process, and that an ideal TMP/F ratio allows an enhancement of the effects of F-containing products (7,8,(10)(11)(12)(13). When TMP and F are co-administered, the adsorption of TMP on the enamel surface can change the selective permeability and facilitate the diffusion of ions such as Ca and F (12) into the enamel (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that TMP reduces the demineralization process, and that an ideal TMP/F ratio allows an enhancement of the effects of F-containing products (7,8,(10)(11)(12)(13). When TMP and F are co-administered, the adsorption of TMP on the enamel surface can change the selective permeability and facilitate the diffusion of ions such as Ca and F (12) into the enamel (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed a higher F content in the enamel after use of this mouthrinse, although the type of F deposits on the enamel has not been identified: loosely bound F (calcium fluoride -CaF 2 ) or firmly bound F (fluorapatite -FA) (11). Other studies demonstrated that an adequate TMP/F ratio can improve the effectiveness of F-based products even at low F concentrations (12)(13)(14). Nevertheless, the mechanism of TMP action is not yet completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…14 The specimens were rinsed thoroughly with deionized water and immersed in artificial saliva, pH 7.0 (10 mL/block) at room temperature for 2 h, between erosive challenges 14 and overnight. The artificial saliva was made according to the Moretto et al 14 study.…”
Section: Erosive Challenge and Treatmentmentioning
confidence: 99%
“…15 The enamel specimens were exposed to one of the pastes immediately after each erosive challenge. 14 The fluoride varnish was applied only once, just before the erosive challenge, to simulate a clinical situation. 12,16,17 Hardness assessment…”
Section: Erosive Challenge and Treatmentmentioning
confidence: 99%
“…Desta forma, o flúor tópico, vernizes fluoretados, flúor gel e suplementação sistêmica podem constituir métodos bastante eficazes no processo de remineralização dentária 5 . A literatura tem apresentado melhores resultados quanto à remineralização quando a concentração de flúor atinge os 5.000 ppm F nos dentifrícios 24 . Em se tratando de aplicação tópica de flúor (ATF), dentre as variáveis analisadas em nosso estudo, esta demonstrou relação estatisticamente significativa em relação à erosão dentária (p=0,012).…”
unclassified